The Influence of Consumer Behavior on Product Purchasing Decisions at Bets Mart in Doromelo Village, Manggelewa District - Jubaidah Jubaidah; Yeye Suhaesty; Risca Ariska Ramadhan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to determine the influence of consumer behavior on purchasing decisions at Bets Mart, a modern retail store located in Doromelo Village, Manggelewa District, Dompu Regency. The research employed a quantitative approach using simple linear regression analysis. Data were collected through questionnaires completed by 100 respondents who had shopped at Bets Mart. The results show that consumer behavior has a positive and significant influence on purchasing decisions, with a t-value of 4.659 and a significance of 0.000. The coefficient of determination (R²) of 0.581 indicates that 58.1% of the variation in purchasing decisions can be explained by consumer behavior, while the remaining 41.9% is influenced by other factors. These findings support theories suggesting that psychological, social, and personal factors influence consumer purchasing behavior.